2017
DOI: 10.1212/wnl.0000000000004235
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antithrombotic treatment in intracranial hemorrhage survivors with atrial fibrillation

Abstract: In observational studies, anticoagulation with VKA is associated with a lower rate of IS than APA or no-ATM without increasing ICH recurrence significantly. A randomized controlled trial is needed to determine the net clinical benefit of anticoagulation in ICH survivors with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 42 publications
0
66
1
4
Order By: Relevance
“…Z powodu braku badań klinicznych należy za każdym razem indywidualnie podejmować decyzję o rozpoczęciu lub kontynuacji (każdego typu) terapii przeciwkrzepliwej u osób, które doświadczyły ICB w czasie terapii przeciwkrzepliwej [5,[94][95][96]. Można rozważać zamknięcie uszka lewego przedsionka, lecz również w tym przypadku brakuje dowodów z badań randomizowanych, co sprawia, że (idealnie) takie leczenie powinno zostać sprawdzone w warunkach randomizowanego badania zaplanowanego w celu zbierania wiarygodnych danych [97].…”
Section: Migotanie Przedsionków U Pacjentów Z Ostrym Udarem W Czasie unclassified
“…Z powodu braku badań klinicznych należy za każdym razem indywidualnie podejmować decyzję o rozpoczęciu lub kontynuacji (każdego typu) terapii przeciwkrzepliwej u osób, które doświadczyły ICB w czasie terapii przeciwkrzepliwej [5,[94][95][96]. Można rozważać zamknięcie uszka lewego przedsionka, lecz również w tym przypadku brakuje dowodów z badań randomizowanych, co sprawia, że (idealnie) takie leczenie powinno zostać sprawdzone w warunkach randomizowanego badania zaplanowanego w celu zbierania wiarygodnych danych [97].…”
Section: Migotanie Przedsionków U Pacjentów Z Ostrym Udarem W Czasie unclassified
“…Importantly, history of ICH was an exclusion criterion in all trials involving direct oral anticoagulants. Recently, a Cochrane systematic review on antithrombotic therapy after ICH identified only two randomized trials involving 121 participants [ 18 ], while a similar meta-analysis of observational studies showed resumption of anticoagulation resulted in lower rates of recurrent ischemic strokes without the cost of increased ICH recurrence [ 19 ]. This highlights the urgency of ongoing prospective, randomized RESTART (ISRCTN71907627)/SoSTART (EudraCT 2016-004121-16), APACHE-AF (NCT02565693) and NASPAF-ICH (NCT02998905) trials to support clinical decision-making in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Cessation of anticoagulation after intracranial bleeding in the setting of atrial fibrillation is associated with ischemic stroke and mortality [66,[76][77][78]. ere are no evidencebased guidelines on the appropriate time to resume NOACs in this subgroup.…”
Section: Resumption Of Noacsmentioning
confidence: 99%